Final Answer:
The sum of the roots for the equation \(2x^2 - 9 = 0\) is \(0\), and the product of the roots is \(-4.5\).
Step-by-step explanation:
To find the sum and the product of the roots of the equation \(2x^2 - 9\), we first need to set it in the standard quadratic form, which is \(ax^2 + bx + c = 0\).
For the equation \(2x^2 - 9\), we can rewrite it as \(2x^2 - 9 = 0\) to satisfy this form. In this case, \(a = 2\), \(b = 0\) (since there is no \(x\) term), and \(c = -9\).
The sum of the roots of a quadratic equation \(ax^2 + bx + c = 0\) is given by the formula \(-b/a\). The product of the roots is given by \(c/a\). Applying these formulas, we get:
1. Sum of the roots:
text{Sum of roots} = \frac{-b}{a} = \frac{-0}{2} = 0
2. Product of the roots:
\text{Product of roots} = \frac{c}{a} = \frac{-9}{2} = -4.5
Therefore, the sum of the roots for the equation \(2x^2 - 9 = 0\) is \(0\), and the product of the roots is \(-4.5\).